Coronin 1B Controls Endothelial Actin Dynamics at Cell–Cell Junctions and Is Required for Endothelial Network Assembly - Werner, Ann-Cathrin; Weckbach, Ludwig T.; Salvermoser, Melanie; Pitter, Bettina; Cao, Jiahui; Maier-Begandt, Daniela; Forné, Ignasi; Schnittler, Hans-Joachim; Walzog, Barbara; Montanez, Eloi (Frontiers in Cell and Developmental Biology, 2020)
Development and homeostasis of blood vessels critically depend on the regulation of endothelial cell-cell junctions. VE-cadherin (VEcad)-based cell-cell junctions are connected to the actin cytoskeleton and regulated by actin-binding proteins. Coronin 1B (Coro1B) is an actin binding protein that controls actin networks at classical lamellipodia. The role of Coro1B in endothelial cells (ECs) is not fully understood and investigated in this study. Here, we demonstrate that Coro1B is a novel component and regulator of cell-cell junctions in ECs. Immunofluorescence studies show that Coro1B colocalizes with VEcad at cell-cell junctions in monolayers of ECs. Live-cell imaging reveals that Coro1B is recruited to, and operated at actin-driven membrane protrusions at cell-cell junctions. Coro1B recruitment to cell-cell junctions is regulated by cytoskeleton tension. By analyzing the Coro1B interactome, we identify integrin linked kinase (ILK) as new Coro1B-associated protein. Coro1B colocalizes with α-parvin, an interactor of ILK, at the leading edge of lamellipodia protrusions. Functional experiments reveal that depletion of Coro1B causes defects in the actin cytoskeleton and cell-cell junctions. Finally, in matrigel vessel network assays, depletion of Coro1B results in reduced network complexity, vessel number and vessel length. Together, our findings point towards a critical role for Coro1B in the dynamic remodeling of endothelial cell-cell junctions and the assembly of vessel networks.